-10(-v+3)+6(v-11)=v+3+6

Simple and best practice solution for -10(-v+3)+6(v-11)=v+3+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10(-v+3)+6(v-11)=v+3+6 equation:


Simplifying
-10(-1v + 3) + 6(v + -11) = v + 3 + 6

Reorder the terms:
-10(3 + -1v) + 6(v + -11) = v + 3 + 6
(3 * -10 + -1v * -10) + 6(v + -11) = v + 3 + 6
(-30 + 10v) + 6(v + -11) = v + 3 + 6

Reorder the terms:
-30 + 10v + 6(-11 + v) = v + 3 + 6
-30 + 10v + (-11 * 6 + v * 6) = v + 3 + 6
-30 + 10v + (-66 + 6v) = v + 3 + 6

Reorder the terms:
-30 + -66 + 10v + 6v = v + 3 + 6

Combine like terms: -30 + -66 = -96
-96 + 10v + 6v = v + 3 + 6

Combine like terms: 10v + 6v = 16v
-96 + 16v = v + 3 + 6

Reorder the terms:
-96 + 16v = 3 + 6 + v

Combine like terms: 3 + 6 = 9
-96 + 16v = 9 + v

Solving
-96 + 16v = 9 + v

Solving for variable 'v'.

Move all terms containing v to the left, all other terms to the right.

Add '-1v' to each side of the equation.
-96 + 16v + -1v = 9 + v + -1v

Combine like terms: 16v + -1v = 15v
-96 + 15v = 9 + v + -1v

Combine like terms: v + -1v = 0
-96 + 15v = 9 + 0
-96 + 15v = 9

Add '96' to each side of the equation.
-96 + 96 + 15v = 9 + 96

Combine like terms: -96 + 96 = 0
0 + 15v = 9 + 96
15v = 9 + 96

Combine like terms: 9 + 96 = 105
15v = 105

Divide each side by '15'.
v = 7

Simplifying
v = 7

See similar equations:

| 54=4x^2-2X-2 | | (6x+2)=(5x+7) | | b*5a=20 | | 3(x+1)=5x-6 | | 4x+7=2-(8x-8) | | 2x+4y+6y-3xy=0 | | 5t+(2t-1)+t=27 | | 26+12-18=x | | 3x(x^2+9)=0 | | pie=7x+2y | | -6w+2=-28 | | -8(a-10)=-8(a-1)+2 | | 12y(y-3)=15y | | (4x+8)-3=92 | | 6a+4b-9a+5ab-8b= | | 12-(.8)(x+15)=4 | | 8-2x=-3 | | -4+3/2x=/2x | | 8x+11=7x+2 | | 24+12-12=x | | 8(4+8n)+2n=-496 | | -7-3y+2=-8y-8 | | -6(2x+5)=-12x-30 | | -8x+5-2x=-5 | | 5(m+6)=18+7m | | y-1=-3 | | 0=49t+-9.8t | | 25+2x=-7(8x+4)+5x | | 6x-2=7x-8 | | 9p^2-9=891 | | -38=-4+2n | | 15-7x=x-6-5x |

Equations solver categories